Reproductive history, hormonal factors and the incidence of hip and knee replacement for osteoarthritis in middle-aged women. Issue 7 (28th October 2008) - Liu, B; Balkwill, A; Cooper, C; Roddam, A; Brown, A; Beral, V
Abstract : Objectives: To examine the effect of reproductive history and use of hormonal therapies on the risk of hip and knee joint replacement for osteoarthritis. Methods: A prospective study of 1.3 million women aged on average 56 years at recruitment and followed-up through linkage to routinely collected hospital admission records was conducted. The adjusted relative risk (RR) of hip and knee replacement for osteoarthritis was examined in relation to parity, age at menarche, menopausal status, age at menopause and use of hormonal therapies. Results: Over a mean of 6.1 person-years of follow-up, 12 124 women had a hip replacement and 9977 a knee replacement. The risk of joint replacement increased with increasing parity and the effect was greater for the knee than the hip: increase in RR of 2% (95% CI 1 to 4%) per birth for hip replacement and 8% (95% CI 6 to 10%) for knee replacement. An early age at menarche slightly increased the risk of hip and knee replacement (relative risk for menarche ⩽11 years versus 12 years, 1.09 (95% CI 1.03 to 1.16) and 1.15 (95% CI 1.08 to 1.22), respectively). Menopausal status and age at menopause were not clearly associated with risk. Current use of postmenopausal hormone therapy was associated with a significant increase in the incidence of hip and knee replacement (RR 1.38 (95% CI 1.30 to 1.46) and RR 1.58 (95% CI 1.48 to 1.69), respectively) while previous use of oral contraceptives was not (RR 1.02 (95% CI 0.98 to 1.06) and RR 1.00 (95% CI 0.96 to 1.04) for hip and knee, respectively). Conclusions: Hormonal and reproductive factors affect the risk of hip and knee replacement, more so for the knee than the hip. The reasons for this are unclear.